1978
DOI: 10.1161/01.res.42.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange after pulmonary thromboemoblization in dogs.

Abstract: SUMMARY Gas exchange following experimental pulmonary thromboembolization was studied with an inert gas elimination technique in 17 dogs. Pulmonary arterial, systemic arterial, and expired gas concentrations of six gases infused intravenously were measured before embolization and 5,10,15,30,60, and 120 minutes after embolization. Distributions of ventilation-perfusion (VA/Q) ratios were derived from the measured concentrations. In all dogs, embolization caused an increase in blood flow and ventilation to VA/Q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 35 publications
0
34
0
1
Order By: Relevance
“…The obliteration of a large portion of the pulmonary vascular bed results in increased blood flow through the remaining pulmonary capillaries. The VA/Q ratios ofthe perfused units thus fall (20). Although it is unlikely that this would lead to units with VA/( ratios as low as 0.01 or below, these units could result from a combination of increased blood flow and airway obstruction.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The obliteration of a large portion of the pulmonary vascular bed results in increased blood flow through the remaining pulmonary capillaries. The VA/Q ratios ofthe perfused units thus fall (20). Although it is unlikely that this would lead to units with VA/( ratios as low as 0.01 or below, these units could result from a combination of increased blood flow and airway obstruction.…”
Section: Resultsmentioning
confidence: 94%
“…result of decreased transit time of blood through a reduced pulmonary capillary bed with resulting failure of alveolar-end capillary equilibration (18). Recently, VA/Q inequality and intrapulmonary shunt have been implicated as causes for the hypoxemia (19)(20)(21). A low cardiac output state with resulting reduction of mixed venous saturation has also been reported (22), but its impact on arterial hypoxemia has not been evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Site A, the COX-1/2 enzyme, was inhibited with ketorolac, and site B, the thromboxane synthase enzyme, was inhibited with furegrelate. Figure 1 shows that one could rationalize that proximal inhibition at the COX-1/2 enzyme might result in decreased substrate that is available to produce vasodilatory prostaglandins (PGI 2 and PGE 2 ), resulting in worsened pulmonary hypertension (34) and ventilation-perfusion relationships (7,33). Also, the location of COX-1/2 suggests that COX-1/2 inhibition might cause arachidonate to be shunted toward the lipoxygenase pathway, resulting in increased synthesis of vasoconstrictive and bronchoconstrictive leukotrienes (28, 38).…”
mentioning
confidence: 99%
“…The V/Q mismatch criterion to diagnose PE is at variance with several studies [33][34][35][36][37] in which the authors showed that ventilation is shifted away from embolized lung regions. 38 The concept that dead space ventilation is not significantly increased in the course of PE 38 was widely held in respiratory pathophysiology before the V/Q scanning approach was developed as it was asserted by Julius H. Comroe, Jr, who, in 1966, 39 foresaw that: "[T]he decrease in wasted ventilation (ventilation to unperfused or poorly perfused lung) helps the patient but hinders the physician in diagnosis."…”
Section: The Pisaped Criteria and Their Application In Reading Perfusmentioning
confidence: 87%